Pedagogical model of forming professional patriotism in students of specialized secondary educational institutions - Zhanna Gennadevna Khimich (Вестник Майкопского государственного технологического университета)
The relevance of the article is due to the need to build a system for the formation of professional patriotism in the general process of vocational training in secondary vocational educational institutions. The purpose of the article is to identify structural components of the pedagogical model of professional patriotism formation among students of secondary vocational schools, to determine conditions for the effectiveness of the model functioning. The research methods used are theoretical analysis, synthesis, generalization, modeling. The author has presented the following results: the basic components of the pedagogical model (target, organizational, substantive and evaluative) have been identified; the goals and objectives of the model implementation have been indicated; pedagogical conditions that contribute to the effectiveness of the functioning of the model have been identified, stages of the pedagogical model implementation have been determined; forms, methods and means of model implementation have been presented; methods and levels for evaluating the effectiveness of the model (high, medium and low levels) have been proposed. The author has noted social and psychological and pedagogical features of students in secondary vocational schools. Conclusions: professional patriotism is an emerging personality trait, the process of professional patriotism formation is a part of the general educational process in an educational institution, the model of professional patriotism formation involves inclusion of special forms, methods, tools and conditions aimed at developing components of professional patriotism in each personality in the educational process.